Upaya Meningkatkan Partisipasi Masyarakat Dalam Kegiatan Pengelolaan Air Bersih di Desa Jedong Kabupaten Malang - Bagus, Nanang; Giri, Etheldreta Poi (Yayasan Lentera Avanya Nagari, 2023)
Village is the smallest political unit in the Indonesian government system, Village also has a very strategic position as a pillar of national development. In the management of Village-Owned Enterprises, community participation is needed, the competence of managers of Village-Owned Enterprises and reliable leaders. In conducting research, what is done by researchers is by using qualitative research. In sharpening research, qualitative research must establish focus. The informant determination technique carried out by the compiler in this preparation is a purposive sampling technique, and in determining data, researchers use triangulation techniques. From the results of research in Jedong Village in carrying out clean water management activities, the village government has efforts to invite the community to carry out clean water management activities, by providing understanding to the community and jointly carrying out clean water management activities, but in clean water management, there are still obstacles, namely lack of community participation